Physiotherapy interventions for pain management in haemophilia: A systematic review. Issue 4 (13th May 2020) - McLaughlin, Paul; Hurley, Michael; Chowdary, Pratima; Khair, Kate; Stephensen, David
Abstract: Purpose: Approximately 35%‐50% of people with haemophilia (PWH) report living with chronic musculoskeletal pain. Although exercise based rehabilitation is effective for pain in other arthritises, there are no published guidelines for management of chronic pain in PWH. This review aims to evaluate and appraise the current evidence of effectiveness of physiotherapy interventions on (a) pain intensity, (b) quality of life (QoL) and (c) function in PWH. Methods: A systematic review of five databases AMED and CINAHL, EMBASE and MEDLINE and PEDro, as well as trial registries, grey literature and hand searching key journals was completed. Included studies were critically appraised and evaluated for risk of bias. The GRADE approach was used to rate the quality of the evidence. Results: Nine trials consisting of 235 participants met the inclusion criteria. All studies had an overall risk of bias with low methodological quality. Meta‐analysis was not possible due to heterogeneity across trials. Studies comparing a range of physiotherapy interventions against no intervention showed no clear beneficial effect on pain intensity or QoL. Only one study, investigating hydrotherapy or land‐based exercise against control, showed positive effect for pain intensity, but rated very low on GRADE assessment. Studies comparing one physiotherapy intervention against another showed no clear benefit on pain intensity, QoL or function. LASER with exercise and hydrotherapy were shown to have some positive effects on pain intensity, but no clear benefit on function. Conclusions: At present, there is limited evidence for the use of physiotherapy interventions in addressing the issue of pain in PWH. Better designed trials with higher quality and explicit methodology along with user involvement are needed to assess the efficacy of any proposed intervention.